Modeling the Causal Relationships of Job Satisfaction Based on Self-Efficacy and Work–Family Conflict among Employees of the Red Crescent Society of Mazandaran Province with the Mediating Role of Mindfulness - Kiakojouri, Roghieh; Najarpour Ostadi, Saeed; Abdi, Reza (Mental Health and Lifestyle Journal, 2026)
The present study aimed to determine the fit of a causal model of job satisfaction based on self-efficacy and work–family conflict among employees of the Red Crescent Society of Mazandaran Province, with the mediating role of mindfulness. The research method was descriptive-correlational and based on structural equation modeling. The statistical population of this study included all employees of the Red Crescent Society of Mazandaran Province in 2025, whose number was reported to be 986 individuals (N = 986). Using convenience sampling, 237 individuals were selected as the statistical sample (n = 237). The instruments used in the study were the standard Minnesota Job Satisfaction Questionnaire by Weiss et al. (1967), the Self-Efficacy Questionnaire by Sherer et al. (1982), the Work–Family Conflict Questionnaire by Carlson et al. (2002), and the Five Facet Mindfulness Questionnaire by Baer et al. (2006). Structural equation modeling was used to analyze the data. The results of examining the model fit indices showed that the structural model of the study had an acceptable fit. In addition, the results of the Pearson correlation coefficient indicated that there was a positive and significant relationship between self-efficacy and job satisfaction (r = 0.42, p < 0.01), a positive and significant relationship between self-efficacy and mindfulness (r = 0.65, p < 0.01), a negative and significant relationship between work–family conflict and job satisfaction (r = -0.36, p < 0.01), a negative and significant relationship between work–family conflict and mindfulness (r = -0.59, p < 0.01), and a positive and significant relationship between mindfulness and job satisfaction (r = 0.76, p < 0.01). In other words, self-efficacy and work–family conflict were related to job satisfaction both through direct paths and through the mediation of mindfulness. Overall, the findings of the study indicate that enhancing self-efficacy and mindfulness while simultaneously reducing work–family conflict can be considered an effective strategy for increasing job satisfaction among Red Crescent employees and may be taken into account by planners and managers of this organization.